OPTIMALISASI KINERJA PERUSAHAAN MELALUI PENERAPAN SISTEM CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS SALESFORCE - Aribowo, Galih Satrio; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the implementation of Salesforce-based Customer Relationship Management (CRM) as a strategy to optimize corporate performance in today’s competitive digital era. The scope covers the fundamental concept of CRM, the advantages and challenges of implementing Salesforce, and a case study of its application in the fictional retail company PT. Niaga Digital Mandiri. The research method employed is a literature review from recent scholarly sources and descriptive analysis of Salesforce adoption in the business sector. The findings indicate that Salesforce enhances operational efficiency, accelerates sales cycles, improves customer satisfaction and retention, and facilitates data-driven decision-making through real-time customer data integration and advanced analytics features. The case study reveals potential sales growth of up to 35% within three months and business expansion by 12% after Salesforce implementation. Key challenges identified include the need for organizational culture adaptation, relatively high initial investment costs, and customer data security concerns. This study concludes that Salesforce is not merely a technological tool but an essential business strategy that supports sustainable competitive advantage, provided it is implemented with proper strategic planning and adequate human resource support.